A journey through the history of Neurogenetics - SILVA, Thiago Yoshinaga Tonholo; PEDROSO, José Luiz; FRANÇA, Marcondes Cavalcante, JUNIOR; BARSOTTINI, Orlando Graziani Povoas (Arquivos de Neuro-Psiquiatria, 2021)
Since the late 19th century, when several inherited neurological disorders were described, the close relationship between Neurology and heredity were well documented by several authors in a pre-genetic era. The term Neurogenetics came to integrate two large sciences and clinical practices: Neurology and Genetics. Neurogenetics is the emerging field that studies the correlation between genetic code and the development and function of the nervous system, including behavioral traits, personality and neurological diseases. In this historical note, a timeline shows the main events and contributors since the first reports of neurogenetic diseases until the current days. In the recent years, neurologists are experiencing much broader use of new genetic diagnosis techniques in clinical practice. Thus, new challenges are arising in diagnostic approach, ethical considerations, and therapeutic options. This article aims to summarize the main historical hallmarks of Neurogenetics, from the pre-DNA era to the present, and the future directions of the field.
Keywords: Genetic Diseases, Inborn; History; Neurology; Genetics